The JWST Early Release Science Program for Direct Observations of Exoplanetary Systems. III. Aperture Masking Interferometric Observations of the Star HIP 65426 at 3.8 μm - Shrishmoy Ray; Steph Sallum; Sasha Hinkley; Anand Sivaramkrishnan; Rachel Cooper; Jens Kammerer; Alexandra Z. Greebaum; Deeparshi Thatte; Tomas Stolker; Cecilia Lazzoni; Andrei Tokovinin; Matthew de Furio; et al. (The Astrophysical Journal Letters)
We present aperture masking interferometry (AMI) observations of the star HIP 65426 at 3.8 μ m, as part of the JWST Direct Imaging Early Release Science program, obtained using the Near Infrared Imager and Slitless Spectrograph instrument. This mode provides access to very small inner working angles (even separations slightly below the Michelson limit of 0.5 λ / D for an interferometer), which are inaccessible with the classical inner working angles of the JWST coronagraphs. When combined with JWST’s unprecedented infrared sensitivity, this mode has the potential to probe a new portion of parameter space across a wide array of astronomical observations. Using this mode, we are able to achieve a 5 σ contrast of Δ m _F380M  ∼ 7.62 ± 0.13 mag relative to the host star at separations ​​​​​≳0 $\mathop{.}\limits^{\unicode{x02033}}$ 07 , and the contrast deteriorates steeply at separations ≲0 $\mathop{.}\limits^{\unicode{x02033}}$ 07. However, we detect no additional companions interior to the known companion HIP 65426b (at separation ∼0 $\mathop{.}\limits^{\unicode{x02033}}$ 82 or $8{7}_{-31}^{+108}\,{\rm{au}}$ ). Our observations thus rule out companions more massive than 10–12 M _Jup at separations ∼10–20 au from HIP 65426, a region out of reach of ground- or space-based coronagraphic imaging. These observations confirm that the AMI mode on JWST is sensitive to planetary mass companions at close-in separations (≳0 $\mathop{.}\limits^{\unicode{x02033}}$ 07), even for thousands of more distant stars at ∼100 pc, in addition to the stars in the nearby young moving groups and associations, as stated in previous works. This result will allow the planning and successful execution of future observations to probe the inner regions of nearby stellar systems, opening an essentially unexplored parameter space.